(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Placenta accreta (PA) is a major life-threating obstetrical burden associated with high morbidity and mortality. This study aims to evaluate the ability of alpha-fetoprotein for prediction of placenta accreta in women with complete placenta previa centeralis. Method: This is a prospective study carried out at Minia Maternity University Hospital, Egypt during the period from October 2017 to March 2019. This study included a total of 100 pregnant women who are admitted to the hospital for CS between 28:38 weeks of gestation. They were classified into 2 groups (50 women per each), group (I) Diffuse PA: include women with diffuse placenta accreta and group (II) Control group: include women with normally implanted placenta. Results: Both groups were comparable regarding age, residence and parity however, diffuse PA group had significantly higher number of cases with ? 4 previous CSs and positive history of placenta previa. Group (I) had lower postoperative heamoglobin and platelet count (p<0.01). Serum alpha-fetoprotein concentration was significantly higher in PA group compared to control (1.33 ± 0.38 vs. 0.66 ± 0.22 MoM, p<0.01). Also, group (I) had higher amount of blood transfused units and longer duration of hospital stay compared to control group (all p<0.01). Incidence of complications was obviously higher in PA group (41 cases, 82%, p<0.01). The results of the predictive value of serum alpha-fetoprotein for placenta accrete revealed that the area under curve (AUC) was 0.958 and the best cutoff was > 0.84 MoM with a sensitivity of 92%, specificity = 82% PPV = 83%, NPV = 87.2% and accuracy of 85% (p<0.01). Conclusion: In conclusion, the results indicate a significant association between elevated serum alphafetoprotein level and placenta accreta. Also, serum alpha-fetoprotein has a high predictive value for placenta accreta in women with complete placenta previa centeralis.